Approach to cycloplegic refraction - Onyeahiri, Collins (Canadian Journal of Optometry, 2024)
Children and younger adults are able to overcome some of the challenges posed by uncorrected refractive errors due to their potent accommodative abilities. However, this potent accommodative ability can significantly affect the precision of their refractive error’s assessment. To overcome this, paediatric cycloplegic refraction becomes indispensable as the prevalence of uncorrected refractive errors among children is on the increase globally. Cycloplegic refraction is the process by which refractive errors are assessed, measured and quantified using a cycloplegic agents such as homatropine and cyclopentolate. Long standing uncorrected refractive errors in children may predispose them to strabismus (squint), amblyopia (lazy eyes), non-optimal vision, asthenopic symptoms like eyestrain, tearing, and could even accelerate myopia progression. This brief review of paediatric cycloplegic refraction is aimed at pointing out some critical steps, methods, and cycloplegic agents essential in carrying out the procedure to meet the growing need for precise refraction outcome and addressing the rising prevalence of paediatric refractive errors, related cases. It also showcases some guidelines for paediatric cycloplegic spectacle prescription dispensing. It involved long years of dedicated clinical input and review of related literatures relevant to the procedure. Cycloplegic refraction is also indicated in the determination of the full hyperopic correction in the management of manifest childhood esotropia, accommodative spasm, amblyopia, anisometropia, uncompensated esophoria; and suspected pseudomyopia. This will guarantee accurate vision treatment, visual health protection, improvement in children’s academic performance, and overall quality of life of the young generation. Through it, a need for advocacy for an evidence-based paediatric eye care practice; interdisciplinary collaboration among eye care professionals, and supporting research and development of new cycloplegic agents and protocols may be created. Keywords: cycloplrgic refraction, accommodation, esotropia, cyclopentolate, pseudomyopia.